Evaluation of Droplet Digital PCR Assay for the Diagnosis of Candidemia in Blood Samples - Chen, Biao; Xie, Yingguang; Zhang, Ning; Li, Wenqiang; Liu, Chen; Li, Dongmei; Bian, Shaodong; Jiang, Yufeng; Yang, Zhiya; Li, Renzhe; Feng, Yahui; Zhang, Xiaojie; et al. (Frontiers in Microbiology, 2021)
Numerous studies have shown that droplet digital PCR (ddPCR) is a promising tool for the diagnosis of pathogens, especially in samples with low concentrations of pathogenic DNA. An early diagnosis of candidemia is critical for the effective treatment of patients. In this study, we evaluated the sensitivity and specificity of ddPCR assay for Candida DNA detection both in vitro by mixing fungal cells with human blood and in vivo by analyzing blood samples from infected mice and patients with suspected candidemia. The results showed that ddPCR assay could detect a minimum of 4.5 DNA copies per reaction in blood samples. ddPCR showed higher sensitivity and specificity for Candida DNA detection than traditional culture and quantitative PCR (qPCR) methods and also exhibited significantly better positive and negative predictive values than the culture and qPCR methods that were commonly used in clinical practice. Hence, our study demonstrates that ddPCR assay is a promising method for the timely diagnosis of candidemia and could be useful for monitoring the treatment of candidemia.